Geração procedural de puzzles para o desenvolvimento de jogos - Santos, Renan de Souza dos (2022)
Puzzle games are known for having a low replayability. One way to increase the replayability of a puzzle game is to use Procedural Content Generation (PCG). This research analyzes several PCG and its applications in different types of video games in order to develop a 2D puzzle game with unlimited stages and guaranteed solvability. To achieve this goal, a design concept for a path-building puzzle game was developed following good practices in puzzle game design. A Constructive-Type Puzzle Generator and a Solver were developed, but the success rate of valid puzzle generations compared to total attempts was relatively low. The game was tested to identify how different aspects of the procedural generation interfered with the game’s difficulty and, in the end, the results of a sequence of performance tests pointed out some potential improvements for the next versions of the Generator.